Editorial - Mirja Satka; Caroline Skehill (Social Work & Society, 2011)
European social work in the 21st century is facing many ongoing transformations, triumphs, challenges and dilemmas. One simple reason why we should always look to our history when grappling with current issues is to remind us that many of the 'current issues' in practice and policy have historical and often transnational antecedents(e.g. Lorenz 1994 and 2006). To know this assures us that whatever the challenges faced, we have some reference point to consider how similar problems were dealt with in different moments and in the various ideological contexts of the transforming European nation states. Indeed there are many arguments which can be made as to why history is important in the present such as: a means of problematising the present; preserving the past; understanding the origins and changing nature of dilemmas such as how one intervenes effectively to protect children; emphasizing continuities and discontinuities across time and space and so on (e.g. Skehill 2008).